Outcome of non‐vitamin K oral anticoagulants in the treatment of left atrial/left atrial appendage thrombus in patients with nonvalvular atrial fibrillation. (4th February 2020) - Lin, Changjian; Quan, Jinwei; Bao, Yangyang; Hua, Wei; Ke, Ming; Zhang, Ning; Jin, Qi; Xie, Yun; Wei, Yue; Ling, Tianyou; Pan, Wenqi; Wu, Liqun; et al.
Abstract: Background: Data comparing dabigatran with rivaroxaban regarding the resolution of left atrial/left atrial appendage (LA/LAA) thrombus in patients with nonvalvular atrial fibrillation (AF) are scarce. This study aimed to compare the efficacy and safety of dabigatran vs rivaroxaban regarding the resolution of LA/LAA thrombus in patients with nonvalvular AF. Methods: This retrospective study enrolled nonvalvular AF patients scheduled to undergo catheter ablation or cardioversion in Shanghai Ruijin Hospital between January 2014 and January 2019. Altogether, 34 patients with LA/LAA thrombus detected by transesophageal echocardiography (TEE) were enrolled. Among them, 12 patients were treated with dabigatran 150 mg bid and the other 22 with rivaroxaban 20 mg qd. Follow‐up TEE was performed within greater than or equal to 3 weeks to less than 6 months of the initial TEE to evaluate the resolution of the LA/LAA thrombus. Results: Baseline patient characteristics were similar in the two groups. Overall, 18 patients (81.8%) in the rivaroxaban group had complete thrombus resolution after 70.3 ± 22.1 treatment days, and 10 patients (83.3%) in the dabigatran group had complete thrombus resolution after 69.3 ± 47.9 treatment days. There was no significant difference between the groups ( P  = .6). TEE showed that the average length, width, and area of thrombus significantly decreased in both groups after treatment, although there was no significant difference in the amount of change in these parameters between the two groups after treatment ( P  = .6). Undissolved thrombus in two patients in the rivaroxaban group did dissolve after switching to dabigatran. Conclusions: The results suggest that both dabigatran and rivaroxaban are potential options for treating LA/LAA thrombus in patients with nonvalvular AF. Dabigatran could be an alternative option for the resolution of LA/LAA thrombus resistant to rivaroxaban.